THE FUTURE OF ACCOUNTING WITH ARTIFICIAL INTELLIGENCE: OPPORTUNITIES AND CHALLENGES - Khaula Lutfiati Rohmah; Aditya Arisudhana; Tri Septa Nurhantoro (Universitas Respati Yogyakarta, 2022)
Artificial intelligence (AI) is one of the remarkable discoveries in the twentieth century. AI is a science related to the creation of machine intelligence capable of performing tasks that previously can only be done by people (Simarmata et al, 2021). It can be said that AI is a breakthrough to create machines that have higher intelligence than machines in general. The current development of AI is aimed at improving learning and problemsolving abilities (Dongre et al, 2020). Accounting is a field that is very suitable for utilizing AI in every part of its information system. AI is expected to be able to help accounting practitioners to improve their performance and develop services they provide. During the development of AI, accounting practices that already adopted AI have resulted in more qualified and diverse outcomes. Various problems that become accounting limitations can be solved with the help of AI, so that the accounting profession can work on a wider area of accounting services, including forensic accounting and financial services and digital investments